Pulmonary transit time measurement by contrast-enhanced ultrasound in left ventricular dyssynchrony - Ingeborg H F Herold; Salvatore Saporito; Massimo Mischi; Hans C van Assen; R Arthur Bouwman; Anouk G W de Lepper; Harrie C M van den Bosch; Hendrikus H M Korsten; Patrick Houthuizen (Echo Research and Practice, 2016)
Background: Pulmonary transit time (PTT) is an indirect measure of preload and left ventricular function, which can be estimated using the indicator dilution theory by contrast-enhanced ultrasound (CEUS). In this study, we first assessed the accuracy of PTT-CEUS by comparing it with dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Secondly, we tested the hypothesis that PTT-CEUS correlates with the severity of heart failure, assessed by MRI and N-terminal pro-B-type natriuretic peptide (NT-proBNP). Methods and results: Twenty patients referred to our hospital for cardiac resynchronization therapy (CRT) were enrolled. DCE-MRI, CEUS, and NT-proBNP measurements were performed within an hour. Mean transit time (MTT) was obtained by estimating the time evolution of indicator concentration within regions of interest drawn in the right and left ventricles in video loops of DCE-MRI and CEUS. PTT was estimated as the difference of the left and right ventricular MTT. Normalized PTT (nPTT) was obtained by multiplication of PTT with the heart rate. Mean PTT-CEUS was 10.5 ± 2.4 s and PTT-DCE-MRI was 10.4 ± 2.0 s (P = 0.88). The correlations of PTT and nPTT by CEUS and DCE-MRI were strong; r = 0.75 (P = 0.0001) and r = 0.76 (P = 0.0001), respectively. Bland–Altman analysis revealed a bias of 0.1 s for PTT. nPTT-CEUS correlated moderately with left ventricle volumes. The correlations for PTT-CEUS and nPTT-CEUS were moderate to strong with NT-proBNP; r = 0.54 (P = 0.022) and r = 0.68 (P = 0.002), respectively. Conclusions: (n)PTT-CEUS showed strong agreement with that by DCE-MRI. Given the good correlation with NT-proBNP level, (n)PTT-CEUS may provide a novel, clinically feasible measure to quantify the severity of heart failure. Clinical Trial Registry: NCT01735838